Opportunities and Challenges of Traditional Tolphit Cake as Gastronomic Tourism in Bantul Regency, Yogyakarta, Indonesia - Saryani,; Nugroho, Setyo Prasiyono; Sri Larasati, (Technium Social Sciences Journal, 2024)
Adrem or "Tolphit" is a traditional Bantul food which is quite unique and has historical value of origin, culture, geographical landscape and complicated cooking methods. This traditional cake is often served at various traditional ceremonies and celebrations or as an accompaniment to tea and coffee in leisure time. This research was carried out using a descriptive research method with a qualitative approach. Data collection techniques used in this research are in-depth interviews, observation, documentation and literature study. Key informants in this research are historians and gastronomists who comprehend the existence of traditional Adrem cakes, while additional informants in this research are traders who produce traditional Adrem cakes. The analysis technique used in this research is an approach which includes data reduction, data presentation, drawing conclusions and verification. The research results show that traditional tolphit/adrem cakes have the opportunity to be used as gastronomic tourism. This opportunity is reflected in producers who always take part in traditional food festivals or exhibitions, making this traditional culinary known widely in the community. Meanwhile, the challenges faced by producers are the lack of publicity in the form of promotions and the government's role in introducing this cake to tourists, which has resulted in this cake being less popular.